Antibacterial Activity against Methicillin-Resistant Staphylococcus aureus of Colloidal Polydopamine Prepared by Carbon Dot Stimulated Polymerization of Dopamine - Maruthapandi, Moorthy (Nanomaterials (Basel), 2019)
A simple one-step process for the polymerization of dopamine has been developed using nitrogen-doped carbon dots (N@C–dots) as the sole initiator. The synthesized amorphous polydopamine (PDA)-doped N@C–dots (PDA–N@C–dots composite) exhibited a negative charge of –39 mV with particle sizes ranging from 200 to 1700 nm. The stable colloidal solution was active against methicillin-resistant Staphylococcus aureus (MRSA), a Gram-negative bacterium. The strong adhesion of the polymer to the bacterial membrane resulted in a limited diffusion of nutrients and wastes in and out of the cell cytosol, which is a generic mechanism to trigger cell death. Another possible route is the autoxidation of the catechol moiety of PDA to form quinone and release reactive oxygen species (ROS) such as superoxide radicle and hydrogen peroxide, two well-known ROS with antimicrobial properties against both Gram-negative and Gram-positive bacteria.